Tendering process at Giat MARA Raub Pahang / Rabiatul Adawiyah Talib - Talib, Rabiatul Adawiyah (2015)
This project report is to present the tendering process for slopes and fences repair work at GIATMARA Raub. Slopes and fences are very important as it is used to protect the buildings from any miscellaneous and distractions. The falling slopes and fences were due to the heavy rain and soil movement. For this report, it will include the tendering process on choosing the best contractor base on their requirements the lowest price. The contractor also should include all the required certificate. This report is based on my experience during practical training when visited the site. Most information is gathered from all personnel that involved inside construction and at the head quarters. The site chosen are GIATMARA Raub, Pahang